Scale levels of damage to the raceway of a spherical roller bearing. (January 2016) - Maruschak, P.O.; Panin, S.V.; Zakiev, I.M.; Poltaranin, M.A.; Sotnikov, A.L.
Abstract: The study determines the parameters of defects generated in a roller bearing used in the link of a mould oscillating mechanism that makes part of a continuous billet-casting machine. The evolution of such defects is described from the perspective of scale levels of deformation and fracture. The studied wear behaviour in the bearing corresponds to false brinelling; the raceways suffer the formation of grooves having the bottom with folded morphology. The mechanisms of deformation and wear of the bearing were analysed using multi-level approach, i.e. at macro-level, from the perspective of the mechanics of a deformable rigid body, at meso-level II, implementing tribological approaches, and at meso-level I, using the methods of indentation, three-dimensional profilometry and fractography. Highlights: Studied the parameters of defects occurring in the linkage lever's roller bearing False brinelling was quantitatively described. Formation of grooves with the bottom having folded relief was investigated. The mechanisms of deformation and wear of the bearing were analysed using multi-level approach.